The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0074-02762011000600001
|View full text |Cite
|
Sign up to set email alerts
|

Chronic phase of Chagas disease: why should it be treated? A comprehensive review

Abstract: The pathogenesis and evolutive pattern of Chagas disease suggests that the chronic phase should be more widely treated in order to (i)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
13

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 108 publications
(93 citation statements)
references
References 29 publications
2
75
1
13
Order By: Relevance
“…In addition, there is apparent suppression of the parasitemia with the current antiparasitic treatment (289) (290) . In turn, the rates of cure and their confirmation depend on several factors, such as the phase and the duration of disease, the age of the patient, the tests used to evaluate therapeutic efficacy, the duration of follow-up after treatment, associated conditions, and the susceptibility of the specific T. cruzi strain to antiparasitic drugs.…”
Section: Antiparasitic Treatment Of Chagas Diseasementioning
confidence: 99%
“…In addition, there is apparent suppression of the parasitemia with the current antiparasitic treatment (289) (290) . In turn, the rates of cure and their confirmation depend on several factors, such as the phase and the duration of disease, the age of the patient, the tests used to evaluate therapeutic efficacy, the duration of follow-up after treatment, associated conditions, and the susceptibility of the specific T. cruzi strain to antiparasitic drugs.…”
Section: Antiparasitic Treatment Of Chagas Diseasementioning
confidence: 99%
“…Several clinical studies have been conducted and hundreds of patients have been treated with nifurtimox or benznidazole, with variations in the results between the studies and the regions where they were carried out. The average cure rate among acute and recent cases is 80%, while it is less than 20% among chronic cases [23][24][25] . A pilot study, the Benefit project -Benznidazole Evaluation for Interruping Trypanosomiasis -an international, multicenter, double-bind, placebo-controlled trial of tripanocidal chronic Chagas heart disease is in course 40,41 .…”
Section: Drugs In Use and New Strategies For Treating Chagas Diseasementioning
confidence: 99%
“…Since 1912, numerous drugs have been used experimentally and in clinical trials for treating Chagas disease [23][24][25]27 35 . On the other hand, in a multicenter study, was demonstrated that treatment with benznidazole had the same suppressive action on parasitemia over 30 or 60 days of treatment 36 .…”
Section: Drugs In Use and New Strategies For Treating Chagas Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…However, 40% can develop organ involvement a long time after the acute infection, characterized by myocardiopathy, megaesophagus, and megacolon. 51 The prevalence of Chagas/HIV coinfection around the world is difficult to establish. 52 Almeida et al 53 published a study involving 716 patients with HIV treated in a University Hospital in Brazil.…”
Section: Chagas Diseasementioning
confidence: 99%